2008
DOI: 10.1159/000141516
|View full text |Cite
|
Sign up to set email alerts
|

PAF, rather than Histamine, Participates in Mouse Anaphylactic Hypotension

Abstract: We determined the roles of platelet-activating factor (PAF) and histamine in anaphylactic hypotension in ovalbumin-sensitized anesthetized BALB/c mice. The effects of PAF and histamine on hemodynamic variables were studied by measuring the systemic arterial (Psa), portal venous (Ppv) and central venous (Pcv) pressures. Intravenous PAF evoked a biphasic Psa response, an initial rapid and transient drop followed by marked hypotension, accompanied by a decrease in Pcv. Histamine caused only mild systemic hypotens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 18 publications
3
28
0
Order By: Relevance
“…For oral treatment with antihistamines, mice received diphenhydramine (first-generation H1R antagonist, 20 mg/kg body weight per day; Sigma), desloratadine (second-generation H1R antagonist 20 mg/kg body weight per day; Essex Pharma, Munich, Germany), cimetidine (H2R antagonist, 100 mg/kg; Sigma), thioperamide (H3R/H4R antagonist, 20 mg/kg; Sigma) or vehicle based on previously reported doses [8,9,10] 10 days before and for 5 days after cecal ligation and puncture (CLP). All drugs were dispersed in 200-ml water bottles, and mice were allowed to drink freely.…”
Section: Methodsmentioning
confidence: 99%
“…For oral treatment with antihistamines, mice received diphenhydramine (first-generation H1R antagonist, 20 mg/kg body weight per day; Sigma), desloratadine (second-generation H1R antagonist 20 mg/kg body weight per day; Essex Pharma, Munich, Germany), cimetidine (H2R antagonist, 100 mg/kg; Sigma), thioperamide (H3R/H4R antagonist, 20 mg/kg; Sigma) or vehicle based on previously reported doses [8,9,10] 10 days before and for 5 days after cecal ligation and puncture (CLP). All drugs were dispersed in 200-ml water bottles, and mice were allowed to drink freely.…”
Section: Methodsmentioning
confidence: 99%
“…28,31,39,40 Serum PAF levels correlate with the severity of anaphylaxis in human subjects and mouse models. 31,41 It is produced and secreted by several types of cells, including mast cells, monocytes, tissue macrophages, platelets, eosinophils, Kupffer cells, endothelial cells, neutrophils, and spermatozoa, 31,39,42,43 and has been found to be active at concentrations as low as 10 212 mol/L, 5 despite its short half-life.…”
Section: Review Of the Specific Role Of Paf In Anaphylaxismentioning
confidence: 99%
“…39,41,42 In mice PAF has been shown to activate and induce degranulation of mouse eosinophils. 44 PAF signaling results from its binding to the PAFR rather than to direct physicochemical effects on the target cell.…”
Section: Review Of the Specific Role Of Paf In Anaphylaxismentioning
confidence: 99%
“…In another example of interaction between multiple MC mediators, combined PAF and H1 inhibition almost completely abolished the hypotension seen in passive systemic anaphylaxis. 100 Recent evidence that PAF also can induce MC degranulation has suggested that PAF may act in an autocrine fashion to augment local or systemic MC degranulation responses. 101 MCs are an important source of cytokines during inflammatory responses.…”
Section: Newly Synthesized Mediators (Second Phase)mentioning
confidence: 99%